2022
DOI: 10.1186/s12889-022-14315-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of tailored behavioral health services for sexual and gender minorities in the United States, 2010 to 2020: a panel analysis

Abstract: Background Research indicates that tailored programming for sexual and gender minority (SGM; e.g., lesbian, gay, bisexual, transgender, queer) people, compared to non-tailored programming, is effective for reducing the disproportionate health burden SGM people experience relative to the general population. However, the availability of SGM-tailored programming is often over-reported and inconsistent across behavioral health (i.e., substance use and mental health) facilities in the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…28 It may very well be the case that geographic sociocultural views affect the availability of programs and services designed to support LGBT people along with policies. 11,12,25,29 Results from our analyses also found that community outreach as a programmatic characteristic is positively associated with providing LGBT-tailored programs at SUD facilities. Research suggests that engaging in community outreach to advertise LGBT-tailored programs can help raise awareness of the SUD treatment facilities providing these services.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…28 It may very well be the case that geographic sociocultural views affect the availability of programs and services designed to support LGBT people along with policies. 11,12,25,29 Results from our analyses also found that community outreach as a programmatic characteristic is positively associated with providing LGBT-tailored programs at SUD facilities. Research suggests that engaging in community outreach to advertise LGBT-tailored programs can help raise awareness of the SUD treatment facilities providing these services.…”
Section: Discussionsupporting
confidence: 60%
“… 28 It may very well be the case that geographic sociocultural views affect the availability of programs and services designed to support LGBT people along with policies. 11 , 12 , 25 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, given the increasingly hostile policy landscape for gender minority people in particular, individual- and interpersonal-level interventions tailored for gender minority people, in addition to policy change, may be especially crucial. A recent study found that a decrease in structural stigma was longitudinally associated with an increase in SGM-tailored programming being offered at substance use treatment facilities ( Cascalheira et al., 2022 ), thereby illustrating the potential of multilevel approaches in addressing alcohol-related health inequities among SGM people. Finally, given the impact of structural stigma on alcohol use among SGM people, clinicians need to be aware of these inequities, incorporate conversations about alcohol use into care for SGM people, and be competent in providing care to SGM people.…”
Section: Discussionmentioning
confidence: 99%